Effectiveness of Prenatal Yoga in Reducing Lower Back Pain and Sciatica in Pregnant Women - Syahrul Syafitri; Ika Yulianti; Agus Purnamasari (GLOBAL HEALTH SCIENCE GROUP, 2024)
Pregnancy has physiological changes such as uterine enlargement, during this period the centre of gravity moves forward and this displacement causes the mother to adjust her standing position. Such posture will depend on muscle strength, weight gain, join relaxion properties, fatigue and pre-pregnancy posture. Pregnant women are projected to have a prevalence of 50% of low back pain, in the first trimester, 40% to 70% in the second trimester. And 70%-80% in the third trimester. Projections of sciatica pain with prevalence rates range from 10% to 25% (Bryndal et al., 2020). This pain can interfere with daily activities such as standing, walking, sitting and sleeping. Yoga is non-pharmacological way to treat pain, and prenatal yoga is a classic form of yoga adapted to the physical needs of pregnant women.  A useful method to reduce pregnancy pain and speed up labor during the third trimester. Yoga is also included in non-pharmacological complementary therapies that relieve pain. The purpose pf this study was determined the effectiveness of prenatal yoga in reducing low back pain and sciatica in third trimester pregnant women in the area of Karang Rejo Public Health Centre. The research method was a quasi-experiment with one group type and interrupted time series design. The sample of this study was 27 respondents, frequency intervention 2 times a week for 2 weeks. The tool used in data collection was a numeric scale observation sheet. The result of this study found of difference in pain before and after doing yoga viewed from the results of paired t-test with p-value=0.000 with an average difference of 5.41. there was an effectiveness felt by pregnant women before and after yoga, with the effectiveness value of 55%. Therefore, the benefits of yoga as complementary therapy can be felt by pregnant women in the health facility.